ILife '08 - Cohen, Michael E. (Apple training series, 2008)
ILife 08 iPhoto, iMovie, GarageBand, iWeb, iDVD In the only Apple-certified guide to iLife '08, the authors have you working miracles with iLife within the first few pages. Featuring footage and images from around the world, this book/DVD combo uses real-life material and practical lessons that you can apply immediately to your own projects. Focused lessons take you step by step through all aspects of iLife '08--everything from organizing and sharing your photo library to creating polished video and soundtracks. Along the way, you'll produce podcasts, websites, blogs, video blogs, and custom DVDs. Master the iLife suite of tools quickly through fun, real-world projects Turn your photos into cards, picture books, calendars, or a web gallery Add motion and sound to your slideshows, then publish them online Create a polished video with transitions, music, and effects Learn "Hollywood-style" techniques for making better videos Build a soundtrack in GarageBand, and learn to score a simple movie Publish Web sites, blogs, podcasts, and DVD menus with ease. SPECIAL NOTE: Before starting the lessons in the book, visit www.peachpit.com/atsilife08 for important lesson file updates